ABOUT ONOMASTIC NAMES IN THE TERRITORY OF SHUMANAY DISTRICT - Kuttimuratova, I. (SCIENCE and SOCIETY, 2023)
This article is devoted to the onomastic names of the Shumanay region of Karakalpakstan. The article informs that there are many different historical places and names in the vast territory of the Shumanay region. Journalists, historians, writers, ethnographers, geographers were the first to deal with toponyms. Some of our onomastic names, which are found in the Shumanay region of Karakalpakstan, have hardly been studied, with the exception of a few in their studies. However, based on some historical data and oral sources, we are convinced that the Shumanay area is rich in many onomastic names.